Proactive Distributed Renewable Energy Resources (DRER) for Powering Tomorrow. - Gautier, Luis; Fikru, Mahelet G. (Springer Nature, 2024)
The production and consumption of cleaner energy by distributed renewable energy resource (DRER) owners, sometimes referred to as prosumers, is expected to increase over the next few decades. With energy storage still remaining a costly investment, DRERs are actively looking for ways to match their peak onsite renewable generation with increased consumption to enhance their self-consumption rate. Despite a growing economics literature presenting energy production–consumption decisions by prosumers, there are not many studies characterizing DRER owners that proactively manage their energy accordingly. Building on past studies, we present a model of a DRER owner that maximizes utility to determine her rate of self-consumption after making energy production and consumption decisions. Our results suggest that a proactive DRER owner exhibits a relatively higher level of self-consumption if she cares enough about the carbon footprint coming from her energy consumption decisions. This points to the need for designing customized policy interventions based on how DRER owners view carbon emissions, ranging from no intervention with higher degrees of carbon disutility to using price incentives to encourage production and consumption of energy by the DRER owner.
Keywords: Recursos energéticos renovables; Tecnología limpia; Carbon emissions; Utility; Energy policy; Smart cities; Green electricity; Energy management